Paulo Freire: teaching for freedom and transformation the philosophical influences on the work of Paulo Freire - Dale, John (Springer eBooks., 2011)
A lack of in-depth philosophical analysis has left an unacceptable deficit in the understanding, appreciating and applying of Paulo Freire's work. This lack of analysis promotes frequent misconceptions and creates superficial practice within education. Indeed, the philosophical assumptions contributing to Freire's critical pedagogy require significant intellectual effort to identify, unravel, and ultimately evaluate on the basis of their epistemic, moral and pedagogical tenability. This book generates a far richer and yet more accessible understanding of Freire's theories. It does so because such important ideas, values and attitudes should not suffer from classroom superficiality. Ideas such as banking education, conscientization and humanization are debased when they are reduced to slogans lacking the intellectual support they deserve. In order to understand such terms and their origins more fully, a more in depth examination of Freire?s concepts and their philosophical origins is desperately needed. This accessible book provides teachers, students and others with precisely such an examination of Freire's ideas on transformative education.